On an unknown path in an era of change: Economic insights from Kyrgyzstan - Barchynai Kimsanova (Universitäts- und Landesbibliothek Sachsen-Anhalt, 2024)
This study examines agricultural and rural development in post-communist Kyrgyzstan through three papers: 1. Food Demand During Revolutions: Analyzes the 2005 and 2010 revolutions' impact on food demand, revealing shifts in expenditure on staples and luxuries. 2: Trade Policy Effects: Shows that agricultural credit subsidies boost trade while tariffs reduce exports using a Melitz-type gravity model. 3. Weather Extremes and Poverty: Assesses the impact of weather extremes on poverty from 2013 to 2020, finding cold winters to be especially harmful to poor households. Recommendations include improving conflict anticipation, reallocating resources to public goods, negotiating tariff reductions, and prioritizing infrastructure for vulnerable regions. The study highlights the need for context-specific insights to guide future research on household responses to transitions and environmental challenges. – – Diese Studie untersucht die landwirtschaftliche und ländliche Entwicklung im postkommunistischen Krigististan anhand von drei Papieren: 1. Lebensmittelnachfrage während Revolutionen: Analysiert die Auswirkungen der Revolutionen von 2005 und 2010 auf die Lebensmittelnachfrage und zeigt Verschiebungen bei den Ausgaben für Grundnahrungsmittel und Luxusgüter. 2. Handelspolitische Effekte: Zeigt mit einem Melitz-Gravitationsmodell, dass Agrarkreditsubventionen den Handel fördern, während Zölle die Exporte reduzieren. 3. Wetterextreme und Armut: Bewertet die Auswirkungen von Wetterextremen auf die Armut von 2013 bis 2020 und stellt fest, dass kalte Winter besonders schädlich für arme Haushalte sind. Empfehlungen umfassen die Verbesserung der Konfliktantizipation, die Umverteilung von Ressourcen zu öffentlichen Gütern, die Verhandlung von Zollsenkungen und die Priorisierung der Infrastruktur in gefährdeten Regionen. Die Studie betont die Notwendigkeit kontextspezifischer Einblicke, um zukünftige Forschungen zu den Reaktionen von Haushalten auf Übergänge und Umweltprobleme zu leiten.
urn:nbn:de:gbv:3:4-1981185920-1186084
Keywords: 330